2014
DOI: 10.2147/ppa.s58631
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for enhancing information, motivation, and skills for self-management behavior changes: a qualitative study of diabetes care for older adults in Korea

Abstract: PurposeTo describe strategies for enhancing information, motivation, and skills related to changes in diabetes self-management behavior among community-dwelling older adults in Korea.Patients and methodsA total of five focus group interviews (three separate focus groups) were conducted with 12 older adults with type 2 diabetes and five diabetes educators. Qualitative content analysis was used.Results“One’s own willingness and ability” emerged as a fundamental belief about the strategies for diabetes self-manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
(51 reference statements)
2
24
0
1
Order By: Relevance
“… 31 34 One possible reason for the feeling of food deprivation is that diet recommendations are either too general, idealistic, or not culture-specific. 5 , 35 With limited clear and practical dietary advice, patients are more likely to strictly and passively follow the instructions, thereby inducing the feeling of food deprivation. To decrease the levels of diet barriers perceived by patients with poor glycemic control, effective diet management intervention programs that provide concrete, practical, and culturally specific diet information (including portion control, meal planning, and food shopping) should be launched.…”
Section: Discussionmentioning
confidence: 99%
“… 31 34 One possible reason for the feeling of food deprivation is that diet recommendations are either too general, idealistic, or not culture-specific. 5 , 35 With limited clear and practical dietary advice, patients are more likely to strictly and passively follow the instructions, thereby inducing the feeling of food deprivation. To decrease the levels of diet barriers perceived by patients with poor glycemic control, effective diet management intervention programs that provide concrete, practical, and culturally specific diet information (including portion control, meal planning, and food shopping) should be launched.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies reported that while older adults participating in their studies perceived experiential knowledge as a positive concept, diabetes educators thought more negatively about it (101),(110). …”
Section: Empirical Support For Sensemaking In Diabetes Self-managementmentioning
confidence: 99%
“…The description of such personal discovery process was present in the many studies in the review (88),(101),(102),(74),(103),(81),(104),(105),(106),(107),(71),(98),(77),(108),(82) Several authors described this mode of learning as experiential learning and suggested that it is more effective than the more traditional learning from experts (101),(87).

“The experiential learning method is more effective, for instance, having a breakfast and exercise meeting where patients can experience diet-related or exercise-related changes in their blood glucose level.

…”
Section: Empirical Support For Sensemaking In Diabetes Self-managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 10 Given these divergent opinions, understanding the facilitating or disturbing factors related to self-management is critical for developing effective programs. 11 Most of the studies regarding these factors were conducted from the perspective of the patients 12 with specific chronic diseases such as diabetes 13 15 in settings other than NHs. Furthermore, most of these studies have been reported in Western countries.…”
Section: Introductionmentioning
confidence: 99%